Modified compound fertilizer and preparation method thereof
By combining humic acid-sodium modified bentonite composite carrier with biodegradable hydrophobic membrane, the problems of nutrient release mismatch and environmental pollution in compound fertilizers are solved, achieving precise controlled release and improved environmental friendliness.
Patent Information
- Application Number
- CN202511158140.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-25
AI Technical Summary
Existing compound fertilizers have many problems in terms of nutrient release characteristics and utilization rate, including the mismatch between the release of nutrients such as nitrogen and potassium and the crop's nutrient requirements, micronutrient antagonism, clumping and environmental pollution risks, and uncontrollable release curves.
A dual slow-release mechanism combining humic acid-sodium modified bentonite composite carrier and biodegradable hydrophobic membrane is adopted. Nutrient release is controlled through interlayer ion exchange of the carrier and microcracks in the hydrophobic membrane, and the fertilizer performance is enhanced by biostimulants.
This technology achieves a nutrient release curve that matches crop needs, improves the compressive strength of compound fertilizer granules, reduces the risk of environmental pollution, and enhances the environmental friendliness and controlled-release precision of fertilizers.
Abstract
Description
Technical Field
[0001] This invention relates to the field of compound fertilizer technology, specifically to a modified compound fertilizer and its preparation method. Background Technology
[0002] As a core production material in modern agriculture, compound fertilizers directly affect crop yield and the ecological environment due to their nutrient release characteristics and utilization rate. With the development of precision agriculture, traditional compound fertilizers have revealed many problems in terms of structural design, nutrient control, and environmental compatibility.
[0003] In conventional compound fertilizers (such as blended and granular types), the release of easily soluble nutrients such as nitrogen and potassium reaches its peak of over 80% within 7-15 days after application, while the peak nutrient requirements of crops during their critical growth stages are mostly between 30-60 days. This time mismatch results in: nitrogen leaching loss exceeding 40%, polluting groundwater; and potassium ions being fixed by soil colloids, with an actual utilization rate of less than 35%. Although existing slow-release technologies (such as sulfur coating and resin coating) can extend the time, they suffer from uncontrollable release curves: a 10°C increase in temperature can increase the release rate of sulfur-coated fertilizers by 3 times, failing to match the dynamic nutrient requirements of crops.
[0004] Micronutrients such as zinc and iron, when directly mixed in an NPK matrix, are prone to chemical antagonism: for example, phosphate ions react with zinc ions to form insoluble Zn3(PO4)2, reducing field availability by 50%–70%; density differences lead to "segregation" during fertilization, resulting in localized micronutrient concentrations below critical values. Existing chelation technologies (such as EDTA-Zn) are costly, and the chelation structure disintegrates at pH > 7.5.
[0005] In a high-humidity environment, the surface of compound fertilizer granules dissolves and recrystallizes to form crystal bridges, and the agglomeration strength reaches 50 N / cm² within 72 hours.
[0006] Ammonium salts (such as NH4Cl) release protons upon deliquescence, catalyzing the hydrolysis of urea to produce biuret toxins. Current anti-caking agents (such as talc and diatomaceous earth) only delay but cannot block crystal bridge formation, and their addition of more than 3% will hinder nutrient release.
[0007] Coating materials pose environmental risks. Petroleum-based polymer coatings (such as polyethylene and polypropylene) have degradation cycles exceeding 200 years, and residual membrane fragments can reduce soil porosity by 23% to 41%. Microplastics can migrate into crop vascular bundles, with levels detected in wheat grains reaching 1.2 mg / kg (EU standard limit 0.5 mg / kg). Bio-based alternatives (such as starch films) have mechanical strength defects: compressive strength <8 MPa, and breakage rate exceeding 30% during field transport. Summary of the Invention
[0008] The purpose of this invention is to provide a modified compound fertilizer and its preparation method, which achieves precise nutrient release by setting a dual slow-release mechanism, so as to match the nutrient release curve with the needs of crops.
[0009] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0010] A modified compound fertilizer, by weight, comprises the following components:
[0011] 55-70 parts of nitrogen, phosphorus and potassium basic fertilizer, 12-18 parts of humic acid-sodium modified bentonite composite carrier, 3-5 parts of polyaspartic acid chelated trace elements, 2-3 parts of biostimulants, and 3-6 parts of biodegradable hydrophobic film.
[0012] Among them, in the nitrogen, phosphorus and potassium basic fertilizer, the mass ratio of nitrogen fertilizer, phosphorus fertilizer and potassium fertilizer is (1.0~1.5):1:(1.0~1.8); the bentonite interlayer spacing in the humic acid-sodium modified bentonite composite carrier is ≥1.65nm; the biodegradable hydrophobic film includes palm wax and sodium lignin sulfonate, with a mass ratio of 2.5~4:1.
[0013] This invention utilizes a humic acid-sodium modified bentonite composite carrier with a bentonite interlayer spacing ≥1.45nm. After loading micronutrient elements into the carrier interlayers, the interlayer spacing can be expanded to 1.82~1.95nm, and the cumulative nitrogen release rate over 60 days is precisely controlled at 75%~80%. The humic acid-bentonite adsorbs phosphate ions into the interlayer, blocking their contact with zinc ions and reducing Zn-P antagonism. The biodegradable hydrophobic membrane surface has 50~80 radial microcracks / mm², with a crack width of 0.5~2μm. Ion exchange between the carrier interlayers controls continuous fertilization for 30~60 days; the biodegradable hydrophobic membrane itself has microcracks, precisely controlling the release rate to <20% in the first 7 days, preventing seedling burn; achieving a dual slow-release mechanism, matching the nutrient release curve with crop needs. The high wax content biodegradable hydrophobic membrane has a compressive strength of 16.2N, effectively reducing field breakage rate, improving membrane strength, and ensuring membrane structural stability.
[0014] Furthermore, the nitrogen fertilizer is selected from at least one of urea or nitrate; the phosphate fertilizer is selected from at least one of monoammonium phosphate or diammonium phosphate; and the potassium fertilizer is selected from at least one of potassium chloride or potassium sulfate.
[0015] Furthermore, the trace elements include zinc, iron, or copper, with a molar ratio of zinc, iron, and copper of 1:(0.8~1.2):(0.3~0.6).
[0016] Furthermore, the biostimulant comprises seaweed extract and gelatinous Bacillus spore powder in a mass ratio of 5-8:1.
[0017] Extraction methods for seaweed extract:
[0018] Extraction process: Wash and chop the seaweed, extract it three times with 10-30 times water or 10%-95% ethanol at 50-100℃, and combine the filtrates;
[0019] Microwave-assisted cell wall disruption: Microwave treatment (800~1200W, 5~10min) accelerates cell wall rupture;
[0020] Compound enzymatic hydrolysis: Cellulase, β-glucanase and papain are added to the concentrate, and enzymatic hydrolysis is carried out at 30°C for 8-12 hours;
[0021] Microbial fermentation: Introduce a complex microbial community (including Aspergillus niger, Lactobacillus plantarum, etc.) and ferment at 25~30℃ for 3~6 days to enhance biological activity.
[0022] Fucoidan in seaweed extract can activate plant PR protein pathways, enhance systemic resistance (SAR), and reduce disease; betaine can maintain cell osmotic balance and improve drought / salt resistance; natural auxin promotes root IAA synthesis, increases root surface area, and enhances nutrient absorption.
[0023] gelatinous Bacillus spore powder: Model HB-02, viable count: 265×10⁻⁶ 8 CFU / g. Gibberellin GA3, a metabolite of Bacillus, breaks seed dormancy and promotes cell elongation; indoleacetic acid (IAA) stimulates lateral root development; antimicrobial peptides inhibit soil-borne pathogens and reduce the incidence of root rot; siderophores / organic acid chelates Fe. 3+ It dissolves and releases insoluble phosphorus and potassium, effectively improving the utilization rate of phosphorus and iron.
[0024] The seaweed polysaccharides in the biostimulant can encapsulate the bacteria, forming a hydrophilic gel layer that blocks the high osmotic pressure of fertilizers and increases the survival rate of the bacteria to 93.2%. The chitinase secreted by the germination of bacterial spores degrades the seaweed cell wall, releasing small molecule oligosaccharides and promoting the enhancement of seaweed polysaccharide activity.
[0025] A preparation method, applicable to the preparation of the modified compound fertilizer, includes the following steps:
[0026] S100 nitrogen, phosphorus and potassium basic fertilizer is sprayed and granulated in a molten state;
[0027] S200, sequentially sprayed with humic acid-sodium modified bentonite composite carrier, polyaspartic acid chelated trace elements and biostimulants, and then dried in a fluidized bed.
[0028] S300: Mix molten palm wax with sodium lignosulfonate, spray the mixture under high pressure onto the surface of the product obtained in step S200, and cure at low temperature to obtain modified compound fertilizer.
[0029] Step S100: Melt spray granulation to construct a porous core: The nitrogen, phosphorus and potassium mixture forms a molten slurry at 132~135℃. When it is atomized and falls through a high-pressure nozzle, the surface tension causes the droplets to shrink into spheres. After cooling and solidification, porous spherical particles (porosity 20~30%) are formed.
[0030] Control the temperature to ≤135℃ to avoid biuret formation and inhibit urea hydrolysis side reactions.
[0031] Step S200: Layered coating forms a layered load. First, a humic acid-bentonite carrier is sprayed, and the bentonite silica tetrahedra adsorb NH4 due to their negative charges. + Humic acid carboxyl chelate Zn 2+ / Fe 2+ This process blocks the antagonistic formation of nitrogen, phosphorus, potassium, and trace elements; then, polyaspartic acid is sprayed to chelate the trace elements, and the carboxyl groups of polyaspartic acid interact with the Al groups on the carrier surface. 3+ Coordination and bonding are formed to create anchorage; finally, biostimulants are sprayed, and the low-temperature (40~45℃) fluidized bed causes the seaweed polysaccharides to form a glassy state, encapsulating the bacterial spores to resist heat damage; presenting a triple structure of carrier adsorption, chelation fixation, and bio-encapsulation, avoiding mutual interference between components.
[0032] In step S300, alternating hot and cold temperatures form a film, creating a self-generated slow-release channel. Molten palm wax (70°C) is sprayed with sodium lignosulfonate, followed by a rapid cooling process at 5-10°C. This triggers the following: the palm wax crystallizes and shrinks, generating radial stress; the glass transition of sodium lignosulfonate is hindered, forming 0.5-2 μm microcracks. Moisture penetrates through these microcracks, dissolving the core nutrients, which are then released through diffusion. The release rate is controlled by the crack density (50-80 cracks / mm²).
[0033] This preparation method systematically solves the three major technical problems that have long existed in the field of compound fertilizers: nutrient antagonism, biological inactivation, and uncontrollable release. It achieves functional decoupling through three-level settings: melt granulation to construct a porous matrix, layered spraying to achieve functional decoupling, and cold and hot film formation to generate controlled release channels.
[0034] Furthermore, the preparation method of the humic acid-sodium modified bentonite composite carrier includes the following steps:
[0035] Step 1: After crushing the bentonite, add sodium carbonate solution and heat to react to obtain sodium-modified bentonite.
[0036] Step 2: After pulverizing the weathered coal powder, add sodium hydroxide solution, heat and react to obtain activated humic acid, dry and grind it into powder;
[0037] Step 3: Add ethanol solution to sodium-modified bentonite, sonicate, add activating humic acid and complexing agent, react, and then treat with microwave radiation.
[0038] Step 1 involves sodium modification of calcium-based bentonite. After pulverizing to 200 mesh, a 4% sodium carbonate solution is added at a solid-liquid ratio of 1:5. The mixture is reacted at 78-82℃ for 2-2.5 hours, centrifuged, washed with water until pH=7.5, and then dried and pulverized at 110℃ for later use. Sodium modification increases the interlayer spacing from 1.25 nm to 1.48 nm, thereby enhancing the humic acid intercalation capacity.
[0039] Step 2: Activation treatment of humic acid: The weathered coal is crushed to 0.2 mm and 10% sodium hydroxide solution is added at a ratio of 1:8; the reaction is carried out at 60~75℃ for 3.5~4.5 hours, the supernatant is collected by centrifugation, and the pH is adjusted to 2.0 with 6M HCl to precipitate humic acid; the precipitate is freeze-dried and then ground into powder (particle size ≤50μm).
[0040] Step 3 employs a synergistic ultrasound-microwave reaction, using thiourea as a complexing agent to generate a composite carrier from sodium-modified bentonite and activated humic acid. Microwaves then bond the carboxyl groups of humic acid to the Al groups between the bentonite layers. 3+ Coordination bonds are formed simultaneously, and the material is dehydrated and solidified. Ultrasonic cavitation disrupts bentonite aggregates, exposing active sites on silicon-oxygen tetrahedra. Microwave non-thermal effects promote the formation of hydrogen bond networks between phenolic hydroxyl groups of humic acid and aluminum-oxygen octahedra of bentonite. The loading rate is increased from 70% by conventional stirring to 93%, and the specific surface area reaches 225 m² / g. Small molecule humic acid (MW < 5 kDa) enters the bentonite interlayer, expanding the interlayer spacing to 1.91 nm. Large molecule humic acid (MW > 20 kDa) undergoes esterification with the -OH groups at the edge of bentonite through -COOH, forming covalent grafts. This enables a dual effect of in-situ intercalation and surface grafting between sodium-modified bentonite and activated humic acid, achieving for the first time a chemical bond between humic acid and bentonite without the participation of synthetic monomers.
[0041] The humic acid-sodium modified bentonite composite carrier is loaded with N, P, K and trace elements to achieve gradient release over 60 days, simultaneously adsorb heavy metals and improve compaction.
[0042] Furthermore, in step 3, the mass ratio of sodium-modified bentonite to activated humic acid is 0.8~1.2:1.
[0043] Furthermore, in step 3, the ultrasonic treatment frequency is 35~45kHz, the time is 30~40min; the heating reaction temperature is 55~65℃, the time is 2~2.5h; the microwave radiation power is 750~800W, the time is 5~8 minutes, and the temperature is controlled below 70℃.
[0044] Furthermore, in step S100, the temperature of melt granulation is 132~135℃, and the particle size is 2~4mm.
[0045] Furthermore, in step S300, the low-temperature curing conditions are: 5~10℃ cold air curing.
[0046] Rapid cooling at 5~10℃ creates radial microcracks, forming an asymmetric structure for controlled release. The radial microcracks, mimicking the structure of plant vessels, enable precise controlled release.
[0047] Compared with the prior art, the beneficial effects of the present invention are:
[0048] This invention utilizes a dual slow-release mechanism achieved through carrier-interlayer ion exchange control and the microcracks inherent in the biodegradable hydrophobic membrane. The cumulative nitrogen release rate over 60 days is less than 80%, ensuring the nutrient release curve matches crop requirements. Simultaneously, it enhances the compressive strength of compound fertilizer granules to 16.2 N, significantly improving soil compaction. The biodegradable membrane formulation balances environmental friendliness with precise controlled release. Furthermore, this invention leverages carrier charge adsorption and chelation bonding to block element antagonism; it integrates a solvent-free, low-energy, and fully biodegradable green preparation process. Detailed Implementation
[0049] Example 1
[0050] The preparation method of humic acid-sodium modified bentonite composite carrier includes the following steps:
[0051] Step 1: Crush 500g of bentonite to 200 mesh, add 4% sodium carbonate solution at a solid-liquid ratio of 1:5, react at 80℃ for 2.1h, centrifuge, wash with water until pH=7.5, dry and pulverize at 110℃ for later use.
[0052] Step 2: Crush the weathered coal to 0.2 mm, add 10% sodium hydroxide solution at a ratio of 1:8; react at 70℃ for 4 hours, centrifuge to collect the supernatant, adjust the pH to 2.0 with 6M HCl to precipitate humic acid; after freeze-drying, grind the precipitate into powder with a particle size of 45 μm;
[0053] Step 3: Add ethanol solution to sodium-modified bentonite, sonicate at 40 kHz for 35 min, the mass ratio of sodium-modified bentonite to activated humic acid is 1:1, add activated humic acid, add 5% complexing agent, react at 60℃ for 2.2 h, then switch to 780W microwave, control the temperature at 65℃, and irradiate for 6 minutes.
[0054] Example 2
[0055] The preparation method of humic acid-sodium modified bentonite composite carrier includes the following steps:
[0056] Step 1: Crush 500g of bentonite to 200 mesh, add 4% sodium carbonate solution at a solid-liquid ratio of 1:4.9, react at 78℃ for 2.5h, centrifuge, wash with water until pH=7.5, dry and pulverize at 108℃ for later use.
[0057] Step 2: Crush the weathered coal to 0.2 mm, add 10% sodium hydroxide solution at a ratio of 1:7.8; react at 75℃ for 3.5 hours, centrifuge to collect the supernatant, adjust the pH to 2.0 with 6M HCl to precipitate humic acid; after freeze-drying, grind the precipitate into powder with a particle size of 40 μm;
[0058] Step 3: Add ethanol solution to sodium-modified bentonite, sonicate at 35 kHz for 40 min, the mass ratio of sodium-modified bentonite to activated humic acid is 0.8:1, add activated humic acid, then add 5% complexing agent, react at 55℃ for 2.5 h, then switch to 800W microwave, control the temperature at 69℃, and irradiate for 5 minutes.
[0059] Example 3
[0060] The preparation method of humic acid-sodium modified bentonite composite carrier includes the following steps:
[0061] Step 1: Crush 500g of bentonite to 200 mesh, add 4% sodium carbonate solution at a solid-liquid ratio of 1:5.1, react at 82℃ for 2 hours, centrifuge, wash with water until pH=7.5, dry and crush at 112℃ for later use.
[0062] Step 2: Crush the weathered coal to 0.2 mm, add 10% sodium hydroxide solution at a ratio of 1:8; react at 60℃ for 4.5 hours, centrifuge to collect the supernatant, adjust the pH to 2.0 with 6M HCl to precipitate humic acid; after freeze-drying, grind the precipitate into powder with a particle size of 50 μm;
[0063] Step 3: Add ethanol solution to sodium-modified bentonite, sonicate at 45 kHz for 30 min, the mass ratio of sodium-modified bentonite to activated humic acid is 1.2:1, add activated humic acid, add 5% complexing agent, react at 65℃ for 25 h, switch to 750W microwave, control the temperature below 60℃, and irradiate for 8 minutes.
[0064] Comparative Example 1
[0065] The preparation method of the humic acid-bentonite composite carrier includes the following steps:
[0066] Step 1: Crush the bentonite to 200 mesh;
[0067] Step 2: Crush the weathered coal to 0.2 mm, add 10% sodium hydroxide solution at a ratio of 1:8; react at 70℃ for 4 hours, centrifuge to collect the supernatant, adjust the pH to 2.0 with 6M HCl to precipitate humic acid; after freeze-drying, grind the precipitate into powder with a particle size of 45 μm;
[0068] Step 3: Add ethanol solution to sodium-modified bentonite, sonicate at 40 kHz for 35 min, the mass ratio of sodium-modified bentonite to activated humic acid is 1:1, add activated humic acid, add 5% complexing agent, react at 60℃ for 2.2 h, then switch to 780W microwave, control the temperature at 65℃, and irradiate for 6 minutes.
[0069] Comparative Example 2
[0070] The preparation method of humic acid-sodium modified bentonite composite carrier includes the following steps:
[0071] Step 1: After crushing the bentonite to 200 mesh, add 4% sodium carbonate solution at a solid-liquid ratio of 1:5, react at 80℃ for 2.1h, centrifuge, wash with water until pH=7.5, dry and crush at 110℃ for later use.
[0072] Step 2: Crush the weathered coal to 0.2 mm, add 10% sodium hydroxide solution at a ratio of 1:8; react at 70℃ for 4 hours, centrifuge to collect the supernatant, adjust the pH to 2.0 with 6M HCl to precipitate humic acid; after freeze-drying, grind the precipitate into powder with a particle size of 45 μm;
[0073] Step 3: Add ethanol solution to sodium-modified bentonite, mechanically stir at 300 rpm, the mass ratio of sodium-modified bentonite to activated humic acid is 1:1, add activated humic acid, then add 5% complexing agent, react at 60℃ for 2.2h, then switch to 780W microwave, control the temperature at 65℃, and irradiate for 6 minutes.
[0074] Comparative Example 3
[0075] The preparation method of humic acid-sodium modified bentonite composite carrier includes the following steps:
[0076] Step 1: After crushing the bentonite to 200 mesh, add 4% sodium carbonate solution at a solid-liquid ratio of 1:5, react at 80℃ for 2.1h, centrifuge, wash with water until pH=7.5, dry and crush at 110℃ for later use.
[0077] Step 2: Crush the weathered coal to 0.2 mm, add 10% sodium hydroxide solution at a ratio of 1:8; react at 70℃ for 4 hours, centrifuge to collect the supernatant, adjust the pH to 2.0 with 6M HCl to precipitate humic acid; after freeze-drying, grind the precipitate into powder with a particle size of 45 μm;
[0078] Step 3: Add ethanol solution to sodium-modified bentonite, sonicate at 40 kHz for 35 min, the mass ratio of sodium-modified bentonite to activated humic acid is 1:1, add activated humic acid, add 5% complexing agent, react at 60℃ for 2.2 h, and dry at 68℃.
[0079] Comparative Example 4
[0080] The preparation method of humic acid-sodium modified bentonite composite carrier includes the following steps:
[0081] Step 1: After crushing the bentonite to 200 mesh, add 4% sodium carbonate solution at a solid-liquid ratio of 1:5, react at 80℃ for 2.1h, centrifuge, wash with water until pH=7.5, dry and crush at 110℃ for later use.
[0082] Step 2: Crush the weathered coal to 0.2 mm, add 10% sodium hydroxide solution at a ratio of 1:8; react at 70℃ for 4 hours, centrifuge to collect the supernatant, adjust the pH to 2.0 with 6M HCl to precipitate humic acid; after freeze-drying, grind the precipitate into powder with a particle size of 45 μm;
[0083] Step 3: Add ethanol solution to sodium-modified bentonite, sonicate at 40 kHz for 35 min, the mass ratio of sodium-modified bentonite to activated humic acid is 1:1, add activated humic acid, then add 5% of the total volume of distilled water, react at 60℃ for 2.2 h, then switch to 780W microwave, control the temperature at 65℃, and irradiate for 6 minutes.
[0084] The performance parameters of the humic acid-sodium modified bentonite composite carriers prepared by the preparation methods of Examples 1-3 and Comparative Examples 1-4 are shown in Table 1.
[0085] Table 1 Performance parameters of humic acid-sodium modified bentonite composite carriers prepared by the preparation methods of Examples 1-3 and Comparative Examples 1-4
[0086] Group Interlayer spacing (XRD) Specific surface area (m² / g) Zn²⁺ adsorption capacity (mg / g) 60-day cumulative nitrogen release rate Example 1 1.87nm 218 142 78% Example 2 1.83nm 205 138 76% Example 3 1.91nm 225 146 80% Comparative Example 1 1.25nm 85 52 94% Comparative Example 2 1.41nm 132 87 89% Comparative Example 3 1.35nm 98 63 92% Comparative Example 4 1.68nm 178 105 85%
[0087] As shown in Table 1, in Examples 1-3, the interlayer spacing of the humic acid-sodium modified bentonite composite carrier can reach 1.83-1.91 nm, and the specific surface area is all >205 m² / g. (Zn) 2+ With an adsorption capacity of 146 mg / g and a cumulative nitrogen release rate of ≤80% over 60 days, it can ensure that the nutrient release curve matches the crop's needs.
[0088] In Comparative Example 1, the lack of sodium modification led to interlayer collapse, while the interlayer of calcium-based bentonite was composed of Ca. 2+ The ions are mainly composed of humic acid with large ionic radii and low hydration energy, which cannot effectively expand the layers. The interlayer spacing is only 1.25 nm, which means that humic acid only adheres to the surface and does not penetrate into the interlayer, reducing the number of adsorption sites. The trace element loading rate is low, only 52 mg / g, and the nitrogen cumulative release rate reaches 94% after 60 days.
[0089] In Comparative Example 2, mechanical stirring replaced ultrasound, resulting in poor dispersion uniformity. Mechanical stirring could not produce cavitation effect, and the agglomeration of bentonite sheets reduced the specific surface area to 132 m² / g.
[0090] In Comparative Example 3, drying instead of microwave drying at 65°C only achieved physical adsorption and did not trigger the coordination bonding between the carboxyl groups of humic acid and the Al³⁺ of bentonite, resulting in an interlayer spacing of only 1.35 nm.
[0091] In Comparative Example 4, the absence of a complexing agent resulted in the loss of chelating sites. The -NH-C=S group of thiourea forms hydrogen bonds with the phenolic hydroxyl group of humic acid, exposing more chelating sites. After omitting these sites, the Zn²⁺ adsorption capacity decreased by 26%, to only 105 mg / g.
[0092] The humic acid-sodium modified bentonite composite carrier of the present invention achieves an interlayer spacing of 1.91 nm and an adsorption capacity 2.7 times that of natural bentonite through a four-step method of sodium-modified layer expansion, ultrasonic dispersion, microwave bonding, and thiourea chelation enhancement.
[0093] Example 4
[0094] A modified compound fertilizer comprises the following components:
[0095] 620g of nitrogen, phosphorus and potassium basic fertilizer, 150g of humic acid-sodium modified bentonite composite carrier prepared by the method in Example 1, 40g of polyaspartic acid chelated trace elements, 24g of biostimulants, and 40g of biodegradable hydrophobic membrane.
[0096] Among them, the mass ratio of nitrogen fertilizer, phosphorus fertilizer and potassium fertilizer in the nitrogen, phosphorus fertilizer and potassium fertilizer is 1.2:1:1.5; the interlayer spacing of bentonite in the humic acid-sodium modified bentonite composite carrier is 1.87nm; the biodegradable hydrophobic film includes palm wax and sodium lignin sulfonate in a mass ratio of 3:1.
[0097] The nitrogen fertilizer consists of urea and nitrate in a 1:1 mass ratio; the phosphate fertilizer is monoammonium phosphate; and the potassium fertilizer is potassium sulfate.
[0098] The molar ratio of zinc, iron and copper in the trace elements is 1:1:0.5.
[0099] The biostimulant comprises seaweed extract and gelatinous Bacillus spore powder in a mass ratio of 7:1.
[0100] A preparation method, applicable to the preparation of the modified compound fertilizer, includes the following steps:
[0101] S100 nitrogen, phosphorus and potassium basic fertilizer is sprayed and granulated in a molten state at 134℃, with a particle size of 3mm.
[0102] S200, sequentially sprayed with humic acid-sodium modified bentonite composite carrier, polyaspartic acid chelated trace elements and biostimulants, and dried in a fluidized bed at 42℃.
[0103] S300: Mix molten palm wax with sodium lignosulfonate, spray the mixture under high pressure onto the surface of the product obtained in step S200, and cure with cold air at 8°C to obtain modified compound fertilizer.
[0104] The method for preparing polyaspartic acid chelated trace elements includes the following steps:
[0105] Step 1: Synthesis of Sodium Polyaspartate
[0106] L-aspartic acid (100g) was mixed with 85% phosphoric acid (40g) and reacted at 220℃ for 3h under nitrogen protection to generate polysuccinimide (PSI). After the PSI was crushed, 10% NaOH solution (500mL) was added and hydrolyzed at 60℃ for 4h to obtain a sodium polyaspartate solution (solid content 30%).
[0107] Purification: Dialysis to remove impurities (molecular weight cutoff 3kDa), freeze-drying to obtain a white powder (molecular weight 8-15kDa).
[0108] Step 2: Stepwise chelation reaction
[0109] 1. Pre-chelated zinc and iron (pH 5.0~6.0):
[0110] Dissolve 40g of ZnSO4·7H2O and 28g of FeSO4·7H2O in 200mL of deionized water; add sodium PASP salt (molecular weight 10kDa, 60g), and stir for 1h at 45℃ and pH=5.5 to generate Zn / Fe-PASP chelate.
[0111] 2. Competitive chelation of copper ions (pH 8.5~9.0): Add CuSO4·5H2O (16g) to the above system and adjust the pH to 8.8;
[0112] Adding thiourea (0.5g) as a competitive ligand inhibits Cu. 2+ The Zn / Fe chelate was replaced, and the reaction was carried out at 60°C for 1.5 h.
[0113] 3. Termination and purification: The reaction solution was spray-dried (inlet air 160℃, outlet air 80℃) to obtain a blue-green powder (Zn:Fe:Cu=1:1:0.5), with a yield of 96.7%.
[0114] Example 5
[0115] A modified compound fertilizer comprises the following components:
[0116] 700g of nitrogen, phosphorus and potassium basic fertilizer, 180g of humic acid-sodium modified bentonite composite carrier prepared by the method in Example 1, 50g of polyaspartic acid chelated trace elements, 30g of biostimulant, and 60g of biodegradable hydrophobic membrane.
[0117] Among them, the mass ratio of nitrogen fertilizer, phosphorus fertilizer and potassium fertilizer in the nitrogen, phosphorus fertilizer and potassium fertilizer is 1.5:1:1.8; the interlayer spacing of bentonite in the humic acid-sodium modified bentonite composite carrier is 1.87nm; the biodegradable hydrophobic film includes palm wax and sodium lignin sulfonate in a mass ratio of 4:1.
[0118] Nitrogen fertilizer is urea; phosphorus fertilizer is diammonium phosphate; potassium fertilizer is potassium chloride.
[0119] Trace elements include zinc, iron, or copper, with a molar ratio of zinc, iron, and copper of 1:1.2:0.6.
[0120] The biostimulant comprises seaweed extract and gelatinous Bacillus spore powder in a mass ratio of 8:1.
[0121] A preparation method, applicable to the preparation of the modified compound fertilizer, includes the following steps:
[0122] S100 nitrogen, phosphorus and potassium basic fertilizer is sprayed and granulated in a molten state at 135℃, with a particle size of 2mm.
[0123] S200, sequentially sprayed with humic acid-sodium modified bentonite composite carrier, polyaspartic acid chelated trace elements and biostimulants, and dried in a fluidized bed at 45℃.
[0124] S300: Mix molten palm wax with sodium lignosulfonate, spray the mixture under high pressure onto the surface of the product obtained in step S200, and cure with cold air at 5°C to obtain modified compound fertilizer.
[0125] The method for preparing polyaspartic acid chelated trace elements includes the following steps:
[0126] Step 1: The synthesis of sodium polyaspartate is the same as in Example 4.
[0127] Step 2: Stepwise chelation reaction:
[0128] 1. Pre-chelated zinc and iron (pH 5.5)
[0129] Dissolve 49.5 g of ZnSO4·7H2O and 58.7 g of FeSO4·7H2O in 200 mL of deionized water;
[0130] Add sodium PASP (73.9 g) and stir to dissolve at 45°C; add 10% H2SO4 dropwise until pH=5.5 ± 0.2, and react for 1 h (the solution changes from turbid to clear).
[0131] 2. Copper ion chelation (pH 8.8)
[0132] Add CuSO4·5H2O (26.3g) and stir to dissolve; add thiourea (2g), dissolve, and adjust the pH to 8.8 ± 0.2 with 10% NaOH; stir at 60℃ for 1.5h (the solution turns dark blue-green).
[0133] 3. Termination and Drying
[0134] Add dilute H2SO4 dropwise until pH=7.0;
[0135] Spray drying:
[0136] With an inlet air temperature of 160℃ and an outlet air temperature of 80℃, a blue-green powder (Zn:Fe:Cu=1:1.2:0.6) was obtained, with a yield of 95.6%.
[0137] Example 6
[0138] A modified compound fertilizer comprises the following components:
[0139] 550g of nitrogen, phosphorus and potassium basic fertilizer, 120g of humic acid-sodium modified bentonite composite carrier prepared by the method in Example 1, 30g of polyaspartic acid chelated trace elements, 20g of biostimulant, and 30g of biodegradable hydrophobic membrane.
[0140] Among them, the mass ratio of nitrogen fertilizer, phosphorus fertilizer and potassium fertilizer in the basic nitrogen, phosphorus fertilizer and potassium fertilizer is 1:1:1; the interlayer spacing of bentonite in the humic acid-sodium modified bentonite composite carrier is 1.87nm; the biodegradable hydrophobic film includes palm wax and sodium lignosulfonate in a mass ratio of 2.5:1.
[0141] Nitrogen fertilizer is nitrate; phosphorus fertilizer is monoammonium phosphate; potassium fertilizer is potassium chloride and potassium sulfate in a mass ratio of 1:1.
[0142] Trace elements include zinc, iron, or copper, with a molar ratio of zinc, iron, and copper of 1:0.8:0.3.
[0143] The biostimulant comprises seaweed extract and gelatinous Bacillus spore powder in a mass ratio of 5:1.
[0144] A preparation method, applicable to the preparation of the modified compound fertilizer, includes the following steps:
[0145] S100 nitrogen, phosphorus and potassium basic fertilizer is sprayed and granulated in a molten state at 132℃, with a particle size of 4mm.
[0146] S200, sequentially sprayed with humic acid-sodium modified bentonite composite carrier, polyaspartic acid chelated trace elements and biostimulants, and then dried in a fluidized bed.
[0147] S300: Mix molten palm wax with sodium lignosulfonate, spray the mixture under high pressure onto the surface of the product obtained in step S200, and cure it with cold air at 10°C to obtain modified compound fertilizer.
[0148] The method for preparing polyaspartic acid chelated trace elements includes the following steps:
[0149] Step 1: The synthesis of sodium polyaspartate is the same as in Example 4.
[0150] Step 2: Stepwise chelation reaction:
[0151] 1. Pre-chelated zinc and iron (pH 5.5)
[0152] Dissolve 66.8 g of ZnSO4·7H2O and 51.7 g of FeSO4·7H2O in 250 mL of deionized water; add 73.2 g of sodium PASP salt and stir at 45 °C to dissolve; add 10% H2SO4 dropwise until pH = 5.5 ± 0.2, and react at 45 °C for 1 h (the solution becomes a clear yellow-green liquid).
[0153] 2. Copper ion chelation (pH 8.8)
[0154] Add CuSO4·5H2O (17.4g) and thiourea (1.3g), stir to dissolve; adjust pH to 8.8 ± 0.2 with 10% NaOH, react at 60℃ for 1.5h (the solution turns blue-green).
[0155] 3. Termination and Drying
[0156] Add dilute H2SO4 dropwise until pH=7.0;
[0157] Spray drying: inlet air 160℃, outlet air 80℃, to obtain blue-green powder (Zn:Fe:Cu=1:0.8:0.3), yield 96%.
[0158] Comparative Example 5
[0159] A modified compound fertilizer comprises the following components:
[0160] 620g of nitrogen, phosphorus and potassium basic fertilizer, 150g of bentonite, 40g of polyaspartic acid chelated trace elements, 24g of biostimulant, and 40g of biodegradable hydrophobic film.
[0161] Among them, the mass ratio of nitrogen fertilizer, phosphorus fertilizer and potassium fertilizer in the nitrogen, phosphorus fertilizer and potassium fertilizer is 1.2:1:1.5; the interlayer spacing of bentonite in the humic acid-sodium modified bentonite composite carrier is 1.87nm; the biodegradable hydrophobic film includes palm wax and sodium lignin sulfonate in a mass ratio of 3:1.
[0162] The nitrogen fertilizer consists of urea and nitrate in a 1:1 mass ratio; the phosphate fertilizer is monoammonium phosphate; and the potassium fertilizer is potassium sulfate.
[0163] The molar ratio of zinc, iron and copper in the trace elements is 1:1:0.5.
[0164] The biostimulant comprises seaweed extract and gelatinous Bacillus spore powder in a mass ratio of 7:1.
[0165] One preparation method is the same as in Example 4.
[0166] Comparative Example 6
[0167] A modified compound fertilizer with the same components, proportions, and parameters as in Example 4.
[0168] A preparation method, applicable to the preparation of the modified compound fertilizer, includes the following steps:
[0169] S100 nitrogen, phosphorus and potassium basic fertilizer is sprayed and granulated in a molten state at 134℃, with a particle size of 3mm.
[0170] S200: After uniformly mixing the humic acid-sodium modified bentonite composite carrier, polyaspartic acid chelated trace elements and biostimulants, the mixture is sprayed onto the surface of the particles prepared in step S100 and dried in a fluidized bed at 42°C.
[0171] S300: Mix molten palm wax with sodium lignosulfonate, spray the mixture under high pressure onto the surface of the product obtained in step S200, and cure with cold air at 8°C to obtain modified compound fertilizer.
[0172] Comparative Example 7
[0173] A modified compound fertilizer comprises the following components:
[0174] 620g of nitrogen, phosphorus and potassium basic fertilizer, 150g of humic acid-sodium modified bentonite composite carrier prepared by the method in Example 1, 40g of polyaspartic acid chelated trace elements, 24g of biostimulants, and 40g of PE resin.
[0175] In the nitrogen, phosphorus, and potassium basic fertilizer, the mass ratio of nitrogen fertilizer, phosphorus fertilizer, and potassium fertilizer is 1.2:1:1.5; the interlayer spacing of bentonite in the humic acid-sodium modified bentonite composite carrier is 1.87 nm.
[0176] The nitrogen fertilizer consists of urea and nitrate in a 1:1 mass ratio; the phosphate fertilizer is monoammonium phosphate; and the potassium fertilizer is potassium sulfate.
[0177] The molar ratio of zinc, iron and copper in the trace elements is 1:1:0.5.
[0178] The biostimulant comprises seaweed extract and gelatinous Bacillus spore powder in a mass ratio of 7:1.
[0179] One preparation method is the same as in Example 4.
[0180] Comparative Example 8
[0181] A modified compound fertilizer with the same components, proportions, and parameters as in Example 4.
[0182] A preparation method, applicable to the preparation of the modified compound fertilizer, includes the following steps:
[0183] S100 nitrogen, phosphorus and potassium basic fertilizer is sprayed and granulated in a molten state at 134℃, with a particle size of 3mm.
[0184] S200, sequentially sprayed with humic acid-sodium modified bentonite composite carrier, polyaspartic acid chelated trace elements and biostimulants, and dried in a fluidized bed at 42℃.
[0185] S300: Mix molten palm wax with sodium lignosulfonate, spray the mixture under high pressure to coat the surface of the product obtained in step S200, and cool naturally at 25°C to obtain modified compound fertilizer.
[0186] The modified compound fertilizers prepared by the methods in Examples 4-6 and Comparative Examples 5-8, after being applied to corn fields, exhibited the following performance parameters, as shown in Table 2.
[0187] Table 2 Performance parameters of the modified compound fertilizers prepared using the methods of Examples 4-6 and Comparative Examples 5-8
[0188] Group Nitrogen utilization rate (%) Compressive strength of particles (N) Spore survival rate (%) 60-day nutrient release rate (%) Soil compaction index Zinc ion leaching rate (%) Available zinc in soil (ppm) Example 4 68.3 15.8 93.2 78 0.29 9.5 42.1 Example 5 66.7 16.2 91.5 76 0.31 10.4 40.3 Example 6 66.9 14.9 92.8 79 0.27 8.9 43.6 Comparative Example 5 41.5 9.3 88.6 94 0.61 56.2 18.0 Comparative Example 6 48.2 11.7 34.1 86 0.53 29.8 26.5 Comparative Example 7 52.7 18.5 89.3 62 0.58 25.1 33.2 Comparative Example 8 56.8 13.2 90.4 92 0.42 34.2 22.7
[0189] As shown in Table 2, in Examples 4-6, the nitrogen fertilizer utilization rate reached 68.3%, the particle compressive strength was 14.9-16.2 N, the spore survival rate was ≥91.5%, the 60-day nutrient release rate was controlled between 75% and 80%, the soil compaction index was 0.27-0.31, the zinc ion leaching rate was less than 10.5%, and the available zinc in the soil was >40 ppm. This indicates that the dual slow-release channels constructed in the modified compound fertilizer of this invention effectively improve nutrient utilization, while simultaneously increasing the particle compressive strength to 16.2 N, significantly improving soil compaction.
[0190] In Comparative Example 5, ordinary bentonite was used instead, with an interlayer spacing of only 1.25 nm and a specific surface area of 85 m² / g. Adsorption was primarily physical, and ordinary bentonite had a smooth surface. (Zn...) 2+ Loose adhesion led to a leaching rate of 56.2%; in Example 4, the modified carrier had a layer spacing of 1.87 nm, a specific surface area of 218 m² / g, and was dominated by chemical chelation, namely humic acid-COOH and Zn. 2+ Complexation, and the modified carrier surface is porous, Zn 2+ Embedded in the humic acid molecular chain, the leaching rate is only 9.5%, effectively breaking the nutrient antagonism.
[0191] In Comparative Example 6, the alkaline environment of the mixed spray carrier caused premature spore germination, and the high temperature (42℃) during fluidized bed drying killed the young bacterial cells, leading to spore inactivation, with a survival rate of 34.1%. The reduced secretion of organic acids by Bacillus subtilis caused the soil pH to rise from 6.8 to 7.4. (Zn) 2+ The zinc ions are converted into Zn(OH)2 precipitate, and are more easily leached away by rainfall. First, a carrier is sprayed to form a porous framework, improving compressive strength, and then bacterial powder is sprayed on top, encapsulating the zinc with seaweed polysaccharides. Furthermore, the layered spraying process indirectly improves zinc retention in the soil by protecting biological activity.
[0192] In Comparative Example 7, the initial release of PE resin from the coating was insufficient, leading to nutrient deficiency in the seedling stage; later, membrane blockage resulted in a release rate of only 62% after 60 days. In Example 4, the release rate after 60 days was 78%, demonstrating that the biodegradable membrane formulation can balance environmental friendliness with precise controlled release.
[0193] In Comparative Example 8, slow cooling at 25℃ caused the palm wax to form dense crystals without radial microcracks and the absence of moisture penetration channels; the release curve showed a 92% release rate after 60 days (close to that of ordinary fertilizer). This indicates that cold air curing at 5~10℃ is a necessary core condition for constructing microcracked slow-release channels.
Claims
1. A modified compound fertilizer, characterized in that, By weight, it includes the following components: 55-70 parts of nitrogen, phosphorus and potassium basic fertilizer, 12-18 parts of humic acid-sodium modified bentonite composite carrier, 3-5 parts of polyaspartic acid chelated trace elements, 2-3 parts of biostimulants, and 3-6 parts of biodegradable hydrophobic film. Among them, in the nitrogen, phosphorus and potassium basic fertilizer, the mass ratio of nitrogen fertilizer, phosphorus fertilizer and potassium fertilizer is (1.0~1.5):1:(1.0~1.8); the bentonite interlayer spacing in the humic acid-sodium modified bentonite composite carrier is ≥1.65nm; the biodegradable hydrophobic film includes palm wax and sodium lignin sulfonate, with a mass ratio of 2.5~4:
1.
2. The modified compound fertilizer according to claim 1, characterized in that, Nitrogen fertilizer is selected from at least one of urea and nitrate; phosphorus fertilizer is selected from at least one of monoammonium phosphate or diammonium phosphate; potassium fertilizer is selected from at least one of potassium chloride or potassium sulfate.
3. The modified compound fertilizer according to claim 1, characterized in that, Trace elements include zinc, iron, or copper, with a molar ratio of zinc, iron, and copper of 1:(0.8~1.2):(0.3~0.6).
4. The modified compound fertilizer according to claim 1, characterized in that, The biostimulant comprises seaweed extract and gelatinous Bacillus spore powder in a mass ratio of 5-8:
1.
5. A preparation method applicable to the preparation of the modified compound fertilizer as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S100 nitrogen, phosphorus and potassium basic fertilizer is sprayed and granulated in a molten state; S200, sequentially sprayed with humic acid-sodium modified bentonite composite carrier, polyaspartic acid chelated trace elements and biostimulants, and then dried in a fluidized bed. S300: Mix molten palm wax with sodium lignosulfonate, spray the mixture under high pressure onto the surface of the product obtained in step S200, and cure at low temperature to obtain modified compound fertilizer.
6. The preparation method according to claim 5, characterized in that, The preparation method of humic acid-sodium modified bentonite composite carrier includes the following steps: Step 1: After crushing the bentonite, add sodium carbonate solution and heat to react to obtain sodium-modified bentonite. Step 2: After pulverizing the weathered coal powder, add sodium hydroxide solution, heat and react to obtain activated humic acid, dry and grind it into powder; Step 3: Add ethanol solution to sodium-modified bentonite, sonicate, then add activating humic acid and complexing agent. After reaction, transfer to microwave irradiation treatment.
7. The preparation method according to claim 6, characterized in that, In step 3, the mass ratio of sodium-modified bentonite to activated humic acid is 0.8~1.2:
1.
8. The preparation method according to claim 6, characterized in that, In step 3, the ultrasonic treatment frequency is 35~45kHz, the time is 30~40min; the reaction temperature is 55~65℃, the time is 2~2.5h; the microwave radiation power is 750~800W, the time is 5~8 minutes, and the temperature is controlled below 70℃.
9. The preparation method according to claim 5, characterized in that, In step S100, the melting and granulation temperature is 132~135℃, and the particle size is 2~4mm.
10. The preparation method according to claim 5, characterized in that, In step S300, the low-temperature curing conditions are: 5~10℃ cold air curing.
Citation Information
Patent Citations
Biological organic-inorganic loss-controlled fertilizer with core-shell structure
CN105481555A
Functional compound fertilizer special for potatoes and preparation method of functional compound fertilizer
CN118878366A
Coated fertilizer, preparation method and application thereof
CN119403776A
Organic-inorganic compound fertilizer containing functional microorganisms and production method of organic-inorganic compound fertilizer
CN120157543A
Plant-source fulvic acid fertilizer and preparation method thereof
CN120483820A